2009
DOI: 10.1007/s10548-009-0109-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain Cortical Mapping by Simultaneous Recording of Functional Near Infrared Spectroscopy and Electroencephalograms from the Whole Brain During Right Median Nerve Stimulation

Abstract: To investigate relationships between hemodynamic responses and neural activities in the somatosensory cortices, hemodynamic responses by near infrared spectroscopy (NIRS) and electroencephalograms (EEGs) were recorded simultaneously while subjects received electrical stimulation in the right median nerve. The statistical significance of the hemodynamic responses was evaluated by a general linear model (GLM) with the boxcar design matrix convoluted with Gaussian function. The resulting NIRS and EEGs data were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 95 publications
(127 reference statements)
2
69
0
Order By: Relevance
“…Similarly, in a simultaneous measurement using fNIRS and EEG, onset and peak delays for Gaussian functions have been adopted for oxy-Hb signal, while deoxy-Hb signal remains to be analyzed. 18 Given this, there is still the need to explore model functions suitable for examining the temporal behaviors of oxy-and deoxy-Hb signals.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a simultaneous measurement using fNIRS and EEG, onset and peak delays for Gaussian functions have been adopted for oxy-Hb signal, while deoxy-Hb signal remains to be analyzed. 18 Given this, there is still the need to explore model functions suitable for examining the temporal behaviors of oxy-and deoxy-Hb signals.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recently, several researchers [3][4][5] have assessed whether NIRS can detect the actual cortical hemodynamic changes associated with neural activation in response to tasks by using NIRS in combination with other methods, such as magnetoencephalography (MEG), transcranial magnetic stimulation (TMS), and electroencephalograms (EEG). Although the results of these studies showed good concordance between NIRS data and those of other modalities, most did not show either short-time or intrinsic (without stimulation) neurohemodynamic processes.…”
Section: Introductionmentioning
confidence: 99%
“…A channel location was defined as the middle point between the corresponding source and detector. The topography was then interpolated on the skin mesh using an inverse distance weighting interpolation scheme as in Aihara et al 65 and Takeuchi et al 66 The topographic maps were finally compared with the maps obtained when using three other arrangements of sources and detectors that we will consider as references.…”
Section: Comparison Of the Optimal Montages With Regular Arrangementsmentioning
confidence: 99%